Effect of rubber insertion on impact behavior of multilayer steel fiber reinforced concrete bulletproof panel. (20th August 2019) - Maho, Buchit; Sukontasukkul, Piti; Jamnam, Sittisak; Yamaguchi, Eiki; Fujikake, Kazunori; Banthia, Nemkumar
Highlights: Rubber insertion can act as a trapping layer to prevent bullet ricocheting. Panels with energy absorption larger than bullet's energy can prevent perforation. Energy absorption depends on thickness, and fiber geometry and volume fraction. Abstract: In this study, the effect of para rubber insertion sheet on impact behavior of multilayer bulletproof panel made of steel fiber reinforced concrete was investigated. The objective of inserting rubber sheet into the middle layer was to act as a trapping layer to prevent bullets from ricocheting off the panel. Two test series were carried out: (1) investigation on energy absorption of each materials and (2) investigation on impact behavior of multilayer panel. The results from the 1st test series were used in the design of multilayer panels used in the 2nd series. The target impact energy of the bullet was 607 J. The multilayer panels were designed to have energy level ranging from 450 to 750 J. The panels were subjected impact by 9 mm caliber bullet with velocity of about 398 m/s. Results showed that the panels with impact energy absorption (IEA) level lower than the kinetic energy of the bullet (607 J.) failed by perforation. The panels with IEA level equal to or higher than 607 J. exhibited penetration failure mode with circular spalling at the back surface. There was no bullet ricocheting that occurred beyond this IEA level. At the level of IEA higher than 672 J, the failure mode shifted to penetration without visible damage at the back surface.